Distribution of Lysosomal Enzymes, Cationic Proteins, and Bactericidal Substances in Subcellular Fractions of Human Polymorphonuclear Leukocytes - Welsh, I. R. H. (1971)
Separation of homogenates of human polymorphonuclear leukocytes (PMN) into different fractions by sedimentation in centrifugal fields that ranged from 126 × g to 50,000 × g resulted in a differential distribution of the lysosomal enzymes. Peroxidase, lysozyme, beta-glucuronidase, and acid phosphatase activity were separated from each other. This demonstrates that the lysosomes of human PMN comprise at least three and possibly four physically and chemically different cytoplasmic particles. Proteins which are more cationic than lysozyme and which may be analogous to cationic lysosomal protein of rabbit PMN were associated with lysozyme and beta-glucuronidase rich granules. Antibacterial activity was present in four of the five cell fractions which this work produced. These results are significant because they differ from those obtained with rabbits and because they directly influence future experimental design and interpretation, in attempts to analyze antibacterial, scavenging, and inflammatory capacities of human PMN. Since lysosomes differ physically, biochemically, and morphologically, they may well differ with respect to their function in the PMN.